Venom composition, toxicity and cross-neutralization by PoliVal-ICP antivenom, of Mesoamerican jumping pitvipers genus Metlapilcoatlus (Viperidae: Crotalinae) - Alfaro Chinchilla, Adriana (2025)
Background: The genus Metlapilcoatlus was recently erected to include six species of stout venomous snakes, known as the jumping pitvipers, which inhabit mountainous areas of Mesoamerica. This group maintains affinity with Atropoides picadoi , another jumping pitviper with restricted distribution in Costa Rica and Panama. Although the venom of A. picadoi and a couple of Metlapilcoatlus species has previously been characterized, little is known about the interspecific and intraspecific variation of the other species that comprise the genus. In this work, we characterize the venoms of five out of the six species that make up the genus Metlapilcoatlus : Metlapilcoatlus indomitus , Metlapilcoatlus mexicanus , Metlapilcoatlus nummifer , Metlapilcoatlus occiduus and Metlapilcoatlus olmec , and for three of them, we analyze whether ontogenetic change occurs in the composition of their venoms. Additionally, we evaluated the cross-neutralizing capacity of the antivenom PoliVal-ICP used in Central American countries to treat viper envenomation. Methods: We utilized sodium dodecyl sulfate–polyacrylamide gel electrophoresis and reverse-phase HPLC for venom characterization. Toxin identification was conducted using a bottom-up shotgun proteomic approach. We also estimated venom toxicity based on average lethality estimates in a murine model. The PoliVal-ICP neu- tralizing capacity on lethal activity was evaluated for all venoms. Using the venom of M. mexicanus as a model, we also tested the neutralizing capacity of this antivenom on hemorrhagic, myotoxic, proteolytic, phospholipase and coagulant activities. Results: Our analysis revealed that the venoms of jumping vipers are composed of proteins belonging to approx- imately 8 −17 families, typically shared with other crotalines. Despite these general similarities, we observed variations at both intraspecific, including ontogenetic, and interspecific levels in venom composition and toxic- ity. The chromatographic pattern of Metlapilcoatlus venom exhibited peaks in the PLA2 /PLA2 -like eluting region, likely responsible for the myotoxic activity of these venoms. By contrast, these peaks were almost negligible in the chromatogram of A. picadoi , whose venom is significantly more hemorrhagic. Among the Metlapilcoatlus species, M. indomitus venom stood out as notably different from the others, and it was also the most lethal. The antivenom demonstrated its effectiveness in neutralizing the lethal activity of all the venoms tested, as well as the various biological activities studied in the venom of M. mexicanus . Conclusions: Beyond the scope of the variation revealed here, our preclinical results demonstrate that PoliVal- ICP antivenom effectively neutralizes toxins from the venom of all Mesoamerican jumping vipers, despite not including venom from any of them in its immunization mixture. This cross-neutralization capacity predicts ICP antivenom’s effectiveness in treating snake envenoming in the Neotropical region.